Association of the Glycated Albumin‐to‐Glycated Haemoglobin Ratio With Mortality in Type 2 Diabetes: A Retrospective Cohort Analysis - Tomohito Gohda; Nozomu Kamei; Marenao Tanaka; Masato Furuhashi; Tatsuya Sato; Mitsunobu Kubota; Michiyoshi Sanuki; Risako Mikami; Koji Mizutani; Yusuke Suzuki; Maki Murakoshi (Endocrinology, Diabetes & Metabolism)
ABSTRACT Introduction The glycated albumin‐to‐glycated haemoglobin (GA/HbA1c) ratio is a potential marker of glycaemic variability; however, its association with adverse clinical outcomes in type 2 diabetes remains unclear. We aimed to determine whether the GA/HbA1c ratio is a better predictor of mortality and chronic kidney disease (CKD) progression than GA alone in type 2 diabetes. Methods This retrospective cohort analysis included 571 Japanese participants with type 2 diabetes who were stratified into tertiles based on their GA/HbA1c ratio. Cox proportional hazards models assessed associations between the GA/HbA1c ratio and mortality or CKD progression (≥ 30% decline in the estimated glomerular filtration rate [eGFR]), adjusting for age, sex, urinary albumin‐to‐creatinine ratio, eGFR, body mass index, haemoglobin and serum albumin. Results In this cohort, the median age was 67 years, and 53.9% were male. During the median follow‐up of 5.4 and 5.3 years for mortality and CKD progression, respectively, 40 (7.0%) participants died and 70 (12.3%) experienced CKD progression. For mortality, the GA/HbA1c ratio demonstrated a U‐shaped association: although both the lowest (T1) and highest (T3) tertiles showed higher mortality risks than the middle tertile (T2), this association was significant for only T3 (hazard ratio, 1.46; 95% CI, 1.05–2.04). Neither GA nor HbA1c alone was significantly associated with mortality. For CKD progression, GA alone showed a U‐shaped association, with both T1 and T3 exhibiting non‐significantly higher risks than T2. Neither the GA/HbA1c ratio nor HbA1c alone was associated with CKD progression. Conclusions In individuals with type 2 diabetes, a higher GA/HbA1c ratio was associated with an increased risk of mortality but not with CKD progression. However, given the retrospective design and limited sample size, these findings should be interpreted with caution and confirmed in larger, prospective studies.